Detección de cambios en la morfología litoral de Punta Zacatal y parte occidental de Isla del Carmen, Campeche, mediante el análisis multitemporal de imágenes de satélite - Alvaro Gerardo Palacio Aponte (Universidad Nacional Autónoma de México, 2001)
During the last 25 years. significant geomorphological changes have been detected in the coastiline of Punta Zacatal and the western region of isla del Carmen, Campeche, as consequence of the current littoral dynamics and the influence of urban and industrial development. In order to detect such changes, a color overlay and composition image analysis was carried out using three Landsat MSS satellite images dated 1974, 1986 and 1992. A near-infrared band (0.8-I.l!~m) was applied to each primary color; assigning color ta high-reflectance values showing changes in land distribution. And absence of color to water bodies and land that remained unchanged. The color presence/absence relationship for each mage allowed to detect coastal accretion, erosion and stable areas in a false-color composite. Aflerwards a supervised classification was canducted to obtain areas and percentages, which were verified by means of multi-temporal photointerpretation and GPS fielidwork validation.